2000
DOI: 10.1039/a908756g
|View full text |Cite
|
Sign up to set email alerts
|

Indoor and outdoor formaldehyde concentrations in homes in residential areas in Greater Cairo

Abstract: Indoor and outdoor measurements of formaldehyde were conducted at seven flats located in residential areas in Greater Cairo, during spring and summer seasons 1999. The mean daytime formaldehyde concentrations in kitchens, bedrooms and living rooms were 89, 100 and 100 ppb, respectively, in the seven flats. Significant positive correlations were found between the concentrations of formaldehyde found in these three rooms. On the other hand, no significant differences were found between the mean formaldehyde conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
6

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 11 publications
1
20
0
6
Order By: Relevance
“…1 However, formaldehyde is one of the important chemicals used in industries for manufacturing building materials and numerous household products. Such usage has recently become a matter of concern as one cause of the sick house syndrome, which is sometimes a very serious problem in Japan.…”
Section: Introductionmentioning
confidence: 99%
“…1 However, formaldehyde is one of the important chemicals used in industries for manufacturing building materials and numerous household products. Such usage has recently become a matter of concern as one cause of the sick house syndrome, which is sometimes a very serious problem in Japan.…”
Section: Introductionmentioning
confidence: 99%
“…Higher concentrations of formaldehyde were observed in May than during the winter. Khoder and Shakour [23] measured formaldehyde at 7 flats in Cairo and found that high concentrations of formaldehyde in summer may be due to the higher emission rate of formaldehyde from its indoor sources at times of relatively higher temperatures and relative humidity. Significant positive correlation coefficients were found between formaldehyde and temperature during seasons in this study.…”
Section: Resultsmentioning
confidence: 99%
“…It is exploited as an adhesive material in pressed wood products, as a preservative in paints and coatings, in the production of fertilizers, paper and plywood, urea-formaldehyde resins and numerous other applications (Yocom Y.E., 1991;Otson, 1992;Khoder, 2000). It is also applied in the production of cosmetics and sugar, in well-drilling fluids, in agriculture as a preservative for grains and seed dressings, in the rubber industry in the production of latex, in leather tanning and in photographic film production.…”
Section: Introductionmentioning
confidence: 99%